Optical scanning - Marshall, Gerald F. (Marcel Dekker, 1991)
Optical Scanning serves as essential reading for optical, electro-optic, electrical and electronics, and laser engineers and designers; optical physicists; and upper-level undergraduate, graduate, and continuing-education students in these disciplines.